Case Report: Cannabis and kratom-induced self-amputation of ears and penis - Broul, Marek; Rudenko, Xenia; Bajus, Adam; Král, Jiří; Kyenge, Dan Mwemena; Staňková, Zdenka; Albrecht, Jakub (Frontiers in Psychiatry, 2025)
This report describes the case of a 31-year-old male lumberjack with severe self-inflicted injuries, including the amputation of both auricles and the penis, under the influence of cannabinoids, mitragynine, and 7-hydroxymitragynine. Emergency surgery was performed, and psychiatric evaluation revealed substance-induced psychosis. The patient’s motivation for reconstructive penile surgery led to abstinence from the substance use and cooperation with treatment. Five months after hospitalization, successful penile reconstruction was completed. The patient remained abstinent and was engaged in regular psychiatric follow-ups, showing no signs of acute psychopathology. This case underscores the importance of using a multidisciplinary approach to manage severe self-harm behaviors, and highlights the critical role of patient motivation in achieving positive outcomes.